Insufficient immune protection in preterm infants due to delayed or incomplete hexavalent vaccination - Kaiser, Elisabeth; Weber, Regine; Bous, Michelle; Fortmann, Ingmar; Dammann, Marie-Theres; Marißen, Janina; Viemann, Dorothee; Derouet, Christoph; Hein, Steve; Nourkami-Tutdibi, Nasenien; Tutdibi, Erol; Wuhrmann, Mara; et al. (Frontiers in Immunology, 2025)
IntroductionFor preterm infants, a 3 + 1 schedule is recommended for hexavalent vaccinations during the first year. The aim of this study was to analyze completion and timeliness of vaccinations in preterm infants of 28 + 0 – 32 + 6 weeks of gestation as part of the PRIMAL study (PRiming of IMmunity At the beginning of Life) and the antibody responses to vaccination antigens.MethodsPlasma antibody-concentrations against poliomyelitis, Haemophilus influenzae type b (Hib), diphtheria and tetanus were determined using ELISA and evaluated with respect to their protectiveness.ResultsAmong 82 patients that were recruited, paired plasma samples on admission and at the one year follow up visit were available in 41 infants. In 17 infants, plasma samples were also collected at two months, prior to the first vaccination. Transplacental antibody transfer yielded protective antibody concentrations against the vaccine antigens in 66% (Hib) to 93% (tetanus) of the infants on admission and in 24% (Polio) to 50% (diphtheria) at 2 months. At the one-year follow-up, all infants who received their vaccinations on time had complete immune protection. However, after one year, hexavalent vaccination was incomplete in 30 of 41 infants (73%). Among incompletely vaccinated infants, the proportion lacking protective antibody concentrations ranged from 12% for diphtheria to 27% for polio.ConclusionsDue to insufficient adherence to vaccination recommendations, 42% of highly vulnerable preterm neonates were insufficiently protected against one or more vaccine-preventable diseases after one year. Efforts should be increased to improve adherence to the recommended 3 + 1 vaccination schedule in preterm infants.